Computer telephony encyclopedia - Grigonis, Richard (New York ; Berkeley, California : CMP Books : Distributed to the book trade in the U.S. and Canada by Publishers Group West, 2000)
"Practical, in-depth, and accessible explanations of essential topics in computer telephony"--Cover.
Includes index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Mobile communication systems -- Encyclopedias; Telephone systems -- Data processing -- Encyclopedias; Digital telephone systems -- Encyclopedias; TCP/IP (Computer network protocol); Internet telephony -- Encyclopedias; Electronic books